Improving Caregiver Competency in Families of Stroke Patients - Husni; Mardiani; Septiyanti; Rukayya Adebisi Abdulrauf (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Stroke patients generally need a long recovery because most individuals undergoing hospital treatment experience disabilities in several parts of the body. Therefore, survivors need the help of other people to live daily life; this role is taken on by caregivers. Caregivers play a crucial role for stroke survivors during the process of long-term rehabilitation and must assume many responsibilities. For this reason, knowledge and skills are needed in caring for post-stroke patients at home. One of the efforts that can be done is through education and training for caregivers and health cadres. This community service activity aimed to enhance cadres’ and caregivers’ knowledge and skill in providing care for families after a stroke. The target population comprised 16 caregivers and seven cadres who supported the families. The results of the community service activities demonstrated an increase in caregivers' knowledge by 32.8 points following the training activities, with a p-value of 0.001 (<α= 0.05), indicating that the difference between the pre- and post-values is statistically significant. The results of observations of cadre and caregiver skills regarding post-stroke care at home include Range of Motion (ROM) exercises, assistance with daily activities, and training in communication in the moderate category. Cadres are expected to continue supporting families as caregivers to be able to care for post-stroke patients at home.